Hubungan Efikasi Diri dengan Keterampilan Petani dalam melakukan Pertolongan Pertama Gigitan Ular di Kecamatan Panti Kabupaten Jember - Icha Yusfi Namami; Wantiyah Wantiyah; Rismawan Adi Yunanto (Pustaka Kesehatan, 2022)
First aid is the provision of immediate help in urgent events. Having self-efficacy can encourage the first aid process. Skills are also considered important to increase self-efficacy in dealing with emergency events. The purpose of this study was to analyze the relationship between self-efficacy and farmer skills in performing snakebite first aid in Panti District, Jember Regency. The research design used correlation with a cross sectional approach. The research sample is 100 respondents with cluster sampling technique. Bivariate analysis used is Spearman rank. The instrument of this research is to use GSE (General Self-Efficacy) and SOP observation sheet for first aid research. The results of this study showed that the respondents' self-efficacy values had a median value of 26 (min-max: 15-40) while the median value of respondents' skills was 16 (min-max: 11-35). Bivariate analysis showed that there was no significant relationship between self-efficacy and farmer skills with the Spearman correlation value of 0.235 (p>0.000). The behavior shown by farmers is they lack self-efficacy and lack of mastery of skills in handling snakebite first aid in the work environment. Keywords: self-efficacy, skills, first aid